Tae kwon do : a guide for athletes and fans - Chandler, Matt (2019)
"In Tae Kwon Do : A Guide for Players and Fans, young readers will jump right into one of the world's oldest sports. Readers will find easy-to-read explanations of tae kwon do's beginnings, basic rules and strategies, and how they can suit up and head to the dojang. This book features colorful photos, fun facts, and informative sidebars, and kids who love martial arts will get closer to earning their first belt with every page!"--
Include bibliographical references and index.
Ages: 8 to 9.
Grades: K to grade 3.
Keywords: Tae kwon do -- Juvenile literature; Tae kwon do